UPAYA MENINGKATKAN PRESTASI BELAJAR IPA PADA MATERI INTERAKSI MAHKLUK HIDUP DENGAN LINGKUNGANNYA MELALUI METODE PEMBELAJARAN DISCOVERY LEARNING - Sadarsih, Ida Meinani (Information Technology Education Department, 2022)
Sciences (IPA) is a national compulsory subject that has several indicators that must be achieved by students. In fact, students of SMP Negeri 2 Muntilan are still in poor category in maximizing their cognition in learning process. Many students do not follow the process, so it has an impact on the results. Based on observations, the students tend to be passive and do not pay attention. In addition, teachers are also still practicing conventional teaching methods. Those are the main factors of the low student learning outcomes. Therefore, researchers compiled classroom action research by applying the Discovery Learning in the learning process. The model is applied to improve science learning achievement for class VIIA of SMP Negeri 2 Muntilan academic year 2019/2020 by focusing on topic of interaction of living things with their environment. The research subjects are 32 students, with the composition of 18 male students and 14 female students. There are two kinds of data, qualitative and quantitative. The qualitative data are taken from observations of teacher and students’ activities, meanwhile the quantitative data is taken from the students’ learning result. The results of the first cycle of the research shows that 100% of students reach the minimum standard score with an average score is 83.65. However, there are 9.3% (3) students who are on the minimum standard score. Meanwhile the results of the second cycle shows the improvement of the students’ result. It shows that all the students get more than minimum standard score with the average score is 87.875. Based on the research findings, it can be concluded that the application of Discovery Learning model can improve the students’ science learning outcome for class VIIA of SMP Negeri 2 Muntilan of academic year 2019/2020 focusing on the interaction of living things with their environment topic.